2017
DOI: 10.1016/j.drugalcdep.2016.08.415
|View full text |Cite
|
Sign up to set email alerts
|

Readiness to change is a predictor of reduced substance use involvement: Findings from a randomized controlled trial of patients attending South African emergency departments

Abstract: Background: This study examines whether readiness to change is a predictor of substance use outcomes and explores factors associated with RTC substance use among patients at South African emergency departments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…A study in South Africa reported positive results for using adapted MI, but showed no difference between MI and controls in treating AUDs in emergency departments . Similar studies using MI have reported good results in Zambia , South Africa and Nigeria . In sub‐Saharan Africa, studies using MI have shown mixed results due to poor attendance to sessions, poor fidelity of the intervention and high attrition rates .…”
Section: Introductionmentioning
confidence: 97%
“…A study in South Africa reported positive results for using adapted MI, but showed no difference between MI and controls in treating AUDs in emergency departments . Similar studies using MI have reported good results in Zambia , South Africa and Nigeria . In sub‐Saharan Africa, studies using MI have shown mixed results due to poor attendance to sessions, poor fidelity of the intervention and high attrition rates .…”
Section: Introductionmentioning
confidence: 97%
“…However, addressing multiple substances in treatment settings is difficult for a variety of reasons [18]. Not the least of which are questions about whether participants are ready and willing to take action to address their polysubstance use [19][20][21]. Indeed, readiness to change is known to be a key predictor for substance use treatment completion [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Our study also explored opportunities for engaging SGM who use CM. Indeed, given the potential harms associated with CM use and polysubstance use, it is important to understand how SGM engage in care or prefer to engage in care [16,20]. In addressing this aim, we asked participants about where they accessed care, who they felt comfortable with approaching them about their substance use, and where they thought we could reach other people who use CM.…”
mentioning
confidence: 99%